2018
DOI: 10.1016/j.jpainsymman.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Medical Assistance in Dying: A Scoping Review of Health Care Providers' Perspectives

Abstract: Evidence from various jurisdictions highlighted a need for clear guidelines and protocols that define each profession's role, scope of practice, and legal boundaries for MAiD. Comprehensive models of care that incorporate multidisciplinary teams alongside improved clinician education may be effective to support MAiD implementation. Little is known about health care providers' perspectives in handling requests, especially outside physician practice and nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 47 publications
7
94
0
1
Order By: Relevance
“…Of particular interest in this review were findings that moral sense‐making in Canadian nurses was a dynamic process characterised by uncertainty and reflection (Beuthin, Bruce, & Scaia, 2018). Other reviews have focused more generally on the experiences of all healthcare providers but revealed similar findings of the emotional impact of MAiD (Fujioka, Mirza, McDonald, & Klinger, 2018) and the need for support and education for nursing, particularly in the ethical aspects of care and in conducting conversations around hastened death (Suva, Penney, & McPherson, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…Of particular interest in this review were findings that moral sense‐making in Canadian nurses was a dynamic process characterised by uncertainty and reflection (Beuthin, Bruce, & Scaia, 2018). Other reviews have focused more generally on the experiences of all healthcare providers but revealed similar findings of the emotional impact of MAiD (Fujioka, Mirza, McDonald, & Klinger, 2018) and the need for support and education for nursing, particularly in the ethical aspects of care and in conducting conversations around hastened death (Suva, Penney, & McPherson, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…8 Notwithstanding that what is known about physicians' experiences in the Canadian context remains scant, a growing body of research from other countries is available. In a recent scoping review, Fujioka et al 9 examined the roles of physicians and other health care professionals in decisionmaking related to MAiD and the professional challenges that arise when they are confronted with patient requests. Key challenges reported by physicians included tensions caused by colleagues conscientiously objecting to MAiD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, Canadian research has largely focused on the understanding of end-of-life legislation, cost analysis, and program implementation (Li et al, 2017;Marcoux, Boivin, Arsenault, Toupin, & Youssef, 2015;Trachtenberg & Manns, 2017). Internationally, a majority of the literature on assisted dying is focused on the physician; however, some research has also examined the roles of nurses and psychiatrists (Block & Billings, 1995;Edwards, 2016;Fujioka, Mirza, McDonald, & Klinger, 2018;Groenewoud et al, 1997;Schwarz, 1999). Much of this literature, however, is focused on opinions related to the ethics of assisted dying, and whether or not the practice is justifiable (Braverman, Marcus, Wakim, Mercurio, & Kopf, 2017;Glebock Gawor, & Ostrowski, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Less explored is the experience of health care professionals working with patients, caregivers, and other providers through the process of MAiD. A scoping review by Fujioka et al (2018) recently investigated the roles of providers involved in MAiD, and the challenges faced by providers involved in the provision of MAiD. This review ultimately concluded that, although a variety of providers are involved in assisted dying, most published literature examines the roles and experiences of physicians and nurses (Fujioka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation